An observational study of Pseudomonas aeruginosa in adult long-term ventilation. Issue 2 (19th April 2022) - Sobala, Ruth; Carlin, Hannah; Fretwell, Thomas; Shakir, Sufyan; Cattermole, Katie; Royston, Amy; McCallion, Paul; Davison, John; Lumb, Joanna; Tedd, Hilary; Messer, Ben; De Soyza, Anthony
Introduction: Pseudomonas aeruginosa increases morbidity and mortality in respiratory disease. To date the long-term ventilation population does not have clear guidelines regarding its management. Method: We undertook a retrospective observational study in a regional long-term ventilation population (837 patients). We defined the primary outcome as P. aeruginosa isolation. In addition positive cultures for copathogens ( Serratia, Proteus species, Stenotrophomonas, Burkholderia cepacia complex and nontuberculous mycobacteria) were recorded . Logistic regression and odds ratios were calculated. Results: 17.6% of the cohort isolated P. aeruginosa, and this pathogen was cultured more frequently in patients with a tracheostomy (logistic regression coefficient 2.90, p≤0.0001) and cystic fibrosis/bronchiectasis (logistic regression coefficient 2.48, p≤0.0001). 6.3% of patients were ventilated via tracheostomy. In the P. aeruginosa positive cohort 46.9% of patients were treated with a long-term macrolide, 36.7% received a nebulised antibiotic and 21.1% received both. Tracheostomised P. aeruginosa positive patients received a nebulised antibiotic more frequently (OR 2.63, 95% CI 1.23–5.64, p=0.013). Copathogens were isolated in 33.3% of the P. aeruginosa cohort. In this cohort patients with a tracheostomy grew a copathogen more frequently than those without (OR 2.75, 95% CI 1.28–5.90). Conclusions: P. aeruginosa isolation is common within the adult long-term ventilation population and is significantly associated with tracheostomy, cystic fibrosis and bronchiectasis. Further research and international guidelines are needed to establish the prognostic impact of P. aeruginosa and to guide on antimicrobial management. The increased risk of P. aeruginosa should be considered when contemplating long-term ventilation via tracheostomy. Pseudomonas aeruginosa isolation is common (17%) in long-term ventilated adults and significantly associated with tracheostomy, cystic fibrosis and bronchiectasis. Tracheostomy patients with P. aeruginosa isolates culture copathogens more frequently. https://bit.ly/3vvxBbB